P155 IMMO-LDRT01 trial: immunomodulatory effects of low dose radiation therapy of chronic degenerative and inflammatory diseases. (March 2019) - Donaubauer, A-J; Gryc, T; Becker, I; Ott, OJ; Fietkau, R; Gaipl, US; Frey, B
Abstract : Career situation of first and presenting author: Student for a master or a PhD. Introduction: The treatment of chronic inflammatory and/or degenerative diseases by low dose radiation therapy (LDRT) is a successful alternative treatment option, especially for patients who were refractory for treatment with drugs. Generally, LDRT aims to reduce pain of patients and to increase their mobility. Although LDRT has successfully been applied since the late 19th century, the underlying immunological mechanisms are only fragmentarily analyzed. Objectives: Therefore we have aimed to analyze the impact of locally delivered LDRT on systemic immune changes. Methods: For this the IMMO-LDRT01 study (NCT02653079 ) was initiated in 2016. The study will include 150 patients suffering from chronic inflammatory and/or degenerative diseases, such as arthritis, arthrosis or benign calcaneodynia. The patients are treated with six local irradiations (single dose per fraction of 0.5Gy) in three weeks. If necessary, the serial irradiation can be repeated after 8–12 weeks, in order to achieve a further reduction of the pain. Blood samples are taken before and after every serial irradiation, as well as during follow-up appointments of the patients. For detailed immunophenotyping of whole blood, we established a multicolor flow cytometry assay, which allows the monitoring of seven main immune cell types, 26 immune cell subtypes, and the activation status of the immune cells. Results: To date 80 patients have been included in the study. First evaluations showed a significant reduction of B cells and cytotoxic T cells in the peripheral blood of patients. In particular, LDRT impacted on activation markers of immune cells. One has to stress that the immunological effects of LDRT were dependent on the particular type of disease of the patients. Currently, the data of the immunophenotyping are correlated to pain perception and quality of life of the patients. Conclusions: These analyses will be helpful to optimize LDRT. A better patient stratification based on pain- and immune-related biomarkers is envisaged for the future, alongside with initiation of deliberated randomized clinical trials. Acknowledgements: This study has been in part funded by the Bundesministerium für Bildung und Forschung (GREWIS and GREWIS-alpha, 02NUK017G and 02NUK050E). Disclosure of Interest: None declared.